Analisis Sektor Perekonomian Kota Aceh Tengah dengan Provinsi Aceh Menggunakan Metode Location Quotient (LQ) Dan Dynamic Location Quotient (DLQ) - Fahrizal Taufiqqurrachman; Anggita Munawaroh; Dessi Lusianti; Ditta Laylia P (Journal of Literature Review, 2026)
Regional economic development requires the identification of leading sectors as a foundation for formulating effective and sustainable development policies. This study aims to analyze base sectors and the dynamics of economic sector development in Aceh Province using the Location Quotient (LQ) and Dynamic Location Quotient (DLQ) methods. The data used consist of Gross Regional Domestic Product (GRDP) data of Aceh Province and Indonesia at constant prices by industrial sector over a specific period. The LQ method is applied to identify base and non-base sectors, while the DLQ method is used to analyze changes and future prospects of economic sectors. The results indicate that several economic sectors function as base sectors in Aceh Province; however, not all base sectors exhibit progressive growth. Meanwhile, the DLQ analysis reveals the presence of potential sectors that are expected to develop and become leading sectors in the future. These findings are expected to serve as a reference for local governments in formulating regional economic development strategies oriented toward strengthening leading sectors and enhancing regional competitiveness.